MUNASABAH AYAT DALAM SURAT AN-NABA’ (Analisis Metodologi Penafsiran Abdullah Darraz Dalam Kitab An-Nabau Al-Azhim Nazharatun Jadidatun Fi Al-Quran) - LUKMANUL HAKIM (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2017)
Muhammad Abdullah Darraz is a contemporary scholars who offer the verses in his concept in his book entitle “Munasabat An-Nabaul Azhim Nazharatun Jadidatun fi Al-Quran” with his theory what called “al-katsrah wa al-wahidah”. This paper intends to knowing more about Darraz’s figure and how hermeneutic framework of Darraz about munasabat the verse, as well as how its application in interpreting the Quran. From this paper known that Muhammad Abdullah Darraz is a contemporary Egypt-born cleric who lived during the French colonization of the turmoil in Egypt which then many aspects influenced his thinking. When it emerged the orientalists who questioned the order structure of the Quran. So, Darraz dispute that assumption with the concept of munasabat verses. Hermeneutic framework of Darraz specifically talking about the munasabat verse in one surah. The point is every letter in al-Quran is the unity of the whole what have one central theme, though composed of diverse themes, this is called the theory of al-katsrah wa al-wahidah on Darraz’s perspective. Each letter is composed of three parts: 1). Opening., 2). Principal purpose, and 3). Closing. And then, Darraz applying the theory of munasabat verse to interpretate sura al-Baqarah entirely. But, in this article, the author tried to examine this theory to interpretate surah an-Naba with using of the offered Darraz theory. From this research, it is known that surat an-naba' consists of Muqaddimmah (found in verses 1-5), with three principal objectives or maqasid (contained in paragraph 6-37), and closing or khatimah (contained in paragraph 38-40)